The Development of the “BEYB” Defensive Tactics Model in Futsal Games - Benny Badaru; Nur indah atifah anwar; Ilham Azis; Hasby Asyhari (AL-ISHLAH: Jurnal Pendidikan, 2022)
Futsal is a game that requires rapid transitions between offensive and defensive methods. The objective of this research is to build a futsal defensive strategy. This study employs a method of development using a model of development created by Brog and Goll. The development phase begins with problem analysis, followed by product design, validation of the designed model, product revision and testing, revision of product test findings, and the obtained model. The expected development is a model for developing futsal defensive strategies known as "BEYB" defensive strategies. The investigation was done at the State University of GOR Futsal FIK Makassar. Participants in this study were futsal players from the city of Makassar. The data collection method leveraged the development phase and administered a different test to up to 120 students. Based on the processed data, the results of this study conclude that there are 30 models of defensive tactics in Futsal, and after testing, that the tactical model produced is viable and effective for usage in Futsal